Soliton Molecules With $± π {{/ 2, 0}}$ , and $π $ Phase Differences in a Graphene-Based Mode-Locked Erbium-Doped Fiber Laser - Lili Gui; Changxi Yang (IEEE Photonics Journal)
A complete collection of two-soliton bound states exhibiting $± π {{/ 2, 0}}$ , and $π $ phase differences was realized in experiment in a mode-locked erbium-doped fiber laser with a graphene saturable absorber for the first time. The graphene mode-locker possesses modulation depth of about 6% and saturation fluency of about 300 μJ/cm2. By carefully adjusting the polarization controller in the laser cavity under appropriate pumping power, diverse soliton molecules with distinct temporal separations and different phase relationships were obtained. Our experimental findings provide clear evidence that stable soliton pairs with $± π {{/ 2, 0}}$ , and $π $ phase differences can be tightly bounded in fiber lasers as intrinsic attractors, which is independent of cavity details such as the mode-locker we choose. In addition, our numerical simulations unravel the influence of nonlinear properties of a saturable absorber on bound states. It is found that mode-lockers with different modulation depth and/or saturation intensity play a role in interpulse separation and individual pulsewidth of generated soliton molecules while keeping the relative phases between bound solitons unchanged. This paper is instructive to explain current research works on bound states in fiber lasers with sorts of saturable absorbers and is of importance to understand the dissipative dynamics of soliton molecules.